2017
DOI: 10.3847/1538-4357/aa6d7c
|View full text |Cite
|
Sign up to set email alerts
|

Using Ice and Dust Lines to Constrain the Surface Densities of Protoplanetary Disks

Abstract: We present a novel method for determining the surface density of protoplanetary disks through consideration of disk "dust lines," which indicate the observed disk radial scale at different observational wavelengths. This method relies on the assumption that the processes of particle growth and drift control the radial scale of the disk at late stages of disk evolution such that the lifetime of the disk is equal to both the drift timescale and growth timescale of the maximum particle size at a given dust line. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
74
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(92 citation statements)
references
References 83 publications
14
74
0
Order By: Relevance
“…Recent multiwavelength observations of disks appear to show signatures of particle drift as the radial extent of several disks becomes smaller at longer wavelengths (e.g., Isella et al 2010;Tripathi et al 2017;Guilloteau et al 2011;Banzatti et al 2011;Pérez et al 2012Pérez et al , 2015Tazzari et al 2016). The radial extent of a disk at a particular wavelength is known as a disk dust line (Powell et al 2017) as, in the millimeter, we can assume that emission at the observed wavelength is dominated by particles with a size comparable to that wavelength. As these particles are all in the Epstein drag regime, the surface density of a given disk can be readily determined given the maximum radius where particles of a given size are present.…”
Section: Arxiv:190503252v1 [Astro-phep] 8 May 2019mentioning
confidence: 98%
“…Recent multiwavelength observations of disks appear to show signatures of particle drift as the radial extent of several disks becomes smaller at longer wavelengths (e.g., Isella et al 2010;Tripathi et al 2017;Guilloteau et al 2011;Banzatti et al 2011;Pérez et al 2012Pérez et al , 2015Tazzari et al 2016). The radial extent of a disk at a particular wavelength is known as a disk dust line (Powell et al 2017) as, in the millimeter, we can assume that emission at the observed wavelength is dominated by particles with a size comparable to that wavelength. As these particles are all in the Epstein drag regime, the surface density of a given disk can be readily determined given the maximum radius where particles of a given size are present.…”
Section: Arxiv:190503252v1 [Astro-phep] 8 May 2019mentioning
confidence: 98%
“…While several studies have suggested that warm gas in the TW Hya disk is CO-depleted by one to two orders of magnitude relative to the ISM (Favre et al 2013;Kama et al 2016;Nomura et al 2016;Schwarz et al 2016;Powell et al 2017), the new high angular resolution ALMA observations provide additional insight into how the CO distribution varies radially.…”
Section: Co Depletion In Warm Gasmentioning
confidence: 99%
“…Estimates for the TW Hya disk's midplane CO snowline location range from 11 to 33 AU Nomura et al 2016;Schwarz et al 2016;Powell et al 2017;van't Hoff et al 2017;Zhang et al 2017), so it is natural to consider whether the apparent steep drop in 12 CO column density at a radius of 15 AU is related. Indeed, several of the aforementioned CO snowline estimates are based on observations of a dip in the C 18 O emission profile at a radius (22 AU) close to where we infer a 12 CO column density drop.…”
Section: Midplane Co Freezeoutmentioning
confidence: 99%
“…It is, however, expected that dust dynamics (in particular radial drift and vertical settling) can change the gas surface density and the location of ice lines (Piso et al 2015;Cleeves 2016;Krijt et al 2016;Powell et al 2017;Stammler et al 2017). In addition, the disk temperature can vary by different effects, such as disk dispersal, which can also change the ice line locations (Panić & Min 2017).…”
Section: Dust Evolution Modelsmentioning
confidence: 99%